INNOVATIVE BUSINESS MODEL DESIGN: A TRIPLE-LAYERED APPROACH FOR INDONESIA'S FASHION SECTOR - Diah Fatma Sjoraida; Nyoman Dwika Ayu Amrita; Endang Ruchiyat (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
The Indonesian fashion industry faces increasingly complex challenges in increasing its competitiveness and sustainability in the global market. To overcome this, the use of technology and innovation is the key to developing adaptive and relevant business models. In this abstract, we explain how technology and innovation can be optimally implemented in fashion business model design to achieve these goals. First, digitalization and e-commerce are the main strategies for optimizing online presence, expanding market reach, and increasing operational efficiency. Second, data analysis and artificial intelligence provide deep insights into consumer trends and market preferences, enabling smarter decisions in business strategy. Third, blockchain technology increases supply chain transparency, strengthening consumer confidence in sustainable and ethical production practices. Fourth, the use of augmented reality (AR) and virtual reality (VR) can improve consumer experiences in online shopping, differentiate fashion brands, and build closer relationships with consumers. Lastly, partnerships with technology startups open access to innovative solutions in logistics, stock management, product development and digital marketing, driving innovation across the Indonesian fashion industry value chain. By holistically integrating technology and innovation in fashion business model design, the Indonesian fashion sector can strengthen its competitiveness in a dynamic global market while improving the sustainability of business practices. It requires investment in digital infrastructure, skilled human resources and a strong culture of innovation in fashion companies to fully exploit the potential of this technology. Thus, adopting technology and innovation with the right approach will bring the Indonesian fashion industry to a higher level in achieving the goals of sustainable competitiveness and sustainability.